Hysteretic behavior of timber framed shear wall with openings - Toğay, Abdullah; Anil, Özgür; Döngel, Ni̇hat; Söğütlü, Cevdet; Isleyen, Ummu Karagoz (Elsevier BV, 2016)
Abstract Hysteretic responses of timber framed shear walls are experimentally investigated in this study. The variables considered in the study are presence of openings with varying dimensions, presence of horizontal retrofitting elements and aspect ratios of timber framed shear walls. The data obtained from the tests conducted on timber framed shear walls are used to deduce conclusions about the behavior of such type panels in terms of load–displacement relationships, strengths, stiffnesses, displacement ductilities, energy dissipation capacities and failure modes. Furthermore, the ultimate loads resisted by the timber framed shear walls are also calculated as per Eurocode 5. Then the analytical and experimental results are comparatively presented. From the test results, it is observed that the aspect ratio of a timber framed shear wall is a significant factor on the load–displacement relationship and failure mode. The varying dimensions of openings on the timber framed shear walls significantly affect the strength and stiffness of the panels. The increasing opening dimensions reduced the strength and stiffness values of the panels. Besides, from the comparison of analytical and experimental results, it is observed that the analytical results are not in good agreement with the experimental results.